Rising to the Top: Evaluating the Use of the HTML META Tag To Improve Retrieval of World Wide Web Documents through Internet Search Engines - Turner, Thomas P; Brackbill, Lise (Library resources & technical services, 1998)
Evaluates the effectiveness of using the HTML META tag to improve retrieval of World Wide Web documents through Internet search engines. Analysis of sample searches suggests that the use of the keywords attribute in a META tag substantially improves accessibility whereas use of the description attribute alone does not. (Author/LRW)